AUTONOMY IN HIGHER EDUCATION - Waghodekar, P H (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
In this paper, it is pointed out that from the time immemorial man is searching ways and means for autonomy, maybe in such matters as spiritual, political, social reformation, discoveries, invention, etc. Autonomy in education is expected to achieve autonomy in other areas of real-life, worldly affairs. In India, the buzz word since the last two decades is autonomy in higher education. We have several models in higher education found and established in Post Graduate (PG) programmes of University, Indian Institute of Technology ( IIT) or Indian Institute of Management ( IIM). These institutions one-way or the other imbibe some elements of autonomy in education. A brief literature review presents some concepts of autonomy and their scope of implementation as perceived worldwide. It is pointed out that the concept of autonomy is being tried out since many decades and researchers have made some proposals to have a better perception of autonomy. An overview of autonomy in higher education in India is presented, as viewed either by UGC or Vice-Chancellors. The author has proposed that a teacher (referred to as a roaming university) is the first link in education chain to be autonomous in a real sense followed by autonomy at such levels as university/institution, management, regulatory bodies, and then at the national level. The author has made some suggestions for each level for inculcating autonomy. For instance, some suggestions are clear national policy, least regulations, reformulation of laws, autonomous management, autonomous institutions awarding degrees, five years teacher’s tenure, lean system, etc. The article will be of interest to all autonomous personnel concerned.